Weed Control in Potato - William M. Stall; Chad M. Hutchinson (EDIS, 2009)
Revised! HS-194, a 3-page fact sheet by William M. Stall and Chad M. Hutchinson, describes effective weed management practices for cultivation of potatoes in Florida, and a table of chemical weed controls. Published by the UF Department of Horticultural Sciences, April 2009.